ANALISIS SPASIAL POTENSI ZAKAT DAN KEMISKINAN DI INDONESIA - Karim, Abdul; Mudhofi, M.; Arwani, Wawan (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2020)
Zakat is one of the alternative instruments in reducing poverty in the region and also increasing the impact on neighborhood area. These effects are commonly called spillover effects. The objective of this study is to analysis spatial dependence of zakat and poverty in Indonesia both globally and locally. To find out the spatial effect so that different regional characteristics have implications for the zakat potential and poverty of each region is different. In this study, spasial analysis uses global Moran's I and Local Indicator Association (LISA), this study uses secondary data sourced from the National Amil Zakat Agency (Baznas) and the Badan Pusat Statistik (BPS) the Republic of Indonesia. Based on the results of spatial dependence, the potential for zakat and poverty in Indonesia is significant and positive, this proves that each region concerned has both in terms of the potential for zakat and poverty.